Three new species of Neocamarosporium isolated from saline environments: N. aestuarinum sp. nov., N. endophyticum sp. nov. and N. halimiones sp. nov. - Gonçalves, M. F. M. (2021)
Neocamarosporium species are typically halotolerant, being commonly found in saline environments like saline water, hypersaline soils and especially in association with halophytes. Several isolates were obtained from saline water, dead leaves of the seaweed Zostera noltii and live tissues of the halophyte Halimione portulacoides. Phylogenetic analysis based on ITS sequence data placed these isolates into three clades within the genus Neocamarosporium distinct from the currently known species. Isolates from each clade showed clear differences in conidial morphology. Three new species N. aestuarinum sp. nov., N. endophyticum sp. nov. and N. halimiones sp. nov. are described and illustrated. Our results show that the salt marsh plant H. portulacoides harbours a high diversity of Neocamarosporium species.